Role of DC-SIGN and L-SIGN receptors in HIV-1 vertical transmission. - da Silva, Ronaldo Celerino; Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
The innate immune system acts in the first line of host defense against pathogens. One of the mechanisms used involves the early recognition and uptake of microbes by host professional phagocytes, through pattern recognition receptors (PRRs). These PRRs bind to conserved microbial ligands expressed by pathogens and initiate both innate and adaptative immune responses. Some PRRs located on the surface of dendritic cells (DCs) and other cells seem to play an important role in human immunodeficiency virus type 1 (HIV-1) transmission. Dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin, CD209 (DC-SIGN) and its homolog, DC-SIGN-related (DC-SIGNR or L-SIGN) receptors are PPRs able to bind the HIV-1 gp120 envelope protein and, because alterations in their expression patterns also occur, they might play a role in both horizontal and vertical transmission as well as in disseminating the virus within the host. This review aims to explore the involvement of the DC-SIGN and L-SIGN receptors in HIV-1 transmission from mother to child.
Keywords: Cell Adhesion Molecules; HIV Infections; HIV-1; Humans; Immunity, Innate; Infectious Disease Transmission, Vertical; Lectins, C-Type; Polymorphism, Genetic; Receptors, Cell Surface